Implementation of Fuzzy-TOPSIS as the Basis for Decision-Making in Purchasing Production Equipment at Plywood Companies - Mubarok, Alvian Alvin; Rahman, Fathi Habibatur; Muhammad, Nadhif (AIBPM Publisher, 2023)
The decision-making process in a company should be based on a strong foundation. A robust decision-making basis is reflected in a methodology that can be accountable, especially in complex cases. Decision-making involving diverse criteria requires a proper methodology to achieve accurate results. Such issues often occur in small or micro-enterprises (SMEs). This study focused on plywood processing companies. The issue at hand was the absence of a standardized method for determining the purchase of production equipment. Therefore, a systematic decision-making tool becomes crucial to reduce the subjectivity among stakeholders. The most crucial production tool in the plywood industry is the press machine. The implementation of Fuzzy TOPSIS successfully provided an objective recommendation. These recommendations are in the form of rankings that inform the highest to lowest recommendations. The Cold Press Machine AKS - IR50T obtained the highest Cci value of 0.75, which can serve as the basis for decision-making in purchasing production equipment.